Model-based requirements engineering - Holt, Jon; Perry, Simon A.; Brownsword, Mike (The Institution of Engineering and Technology, 2012)
This book provides a hands-on introduction to model based requirement engineering and management by describing a set of views that form the basis for the approach. These views take into account each individual requirement in terms of its description, but then also provide each requirement with the meaning by putting it into the correct context. A requirement that has been put into a context is known as a 'use case' and may be based upon either stakeholders or levels of hierarchy in a system. Each use case must then be analysed and validated by defining a combination of scenarios and formal mathematical and logic based proofs that provide the rigour required for safety-critical and mission-critical systems. The book also looks at the crucial question of modelling notations for requirements modelling and includes discussions on the use and application of sysML, text and tabular formats. Pragmatics issues, such as tailoring the approach for short, non-critical projects to massive, mission-critical projects is discussed to show how the techniques introduced in the book can be applied on real life projects and systems. The use of multiple tools can be discussed, along with examples of how an effective process can lead to realisation by any tool.